IMPACT OF RAPID EYE MOVEMENT SLEEP DEPRIVATION ON HYPOTHALAMIC-PITUITARYTESTICULAR AXIS IN WISTAR ALBINO RATS - Jayamurali, Dheepthi; Govindarajulu, Sathya Narayanan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The objectives of the study were to study the impact of rapid eye movement (REM) sleep deprivation (SD) on the hypothalamic-pituitary-testicular (HPT) axis in the Wistar albino rats. Methods: Adult male Wistar albino rats weighing about 200 g were segregated into Group I–IV of control, 48 h SD, 72 h SD, and 96 h SD, respectively, in a custom-made SD tank. After SD procedure, the sexual behavior of rats was assessed, after which blood was collected from the animals for the estimation of HPT and stress hormones and then the testicles were used for histological studies. Results: SD has increased (p<0.05) the mounting latency and intromission latency and decreased (p<0.05) the mounting frequency and intromission frequency compared with control group. A significant increase (p<0.05) in corticosterone, follicle stimulating hormone levels and a significant decrease (p<0.05) in gonadotropin-releasing hormone, luteinizing hormone and testosterone levels were observed in all the SD groups when compared with control group. SD-induced testis architecture displayed sperm retention, sperm reduction, and shape alteration when compared to the control group. Furthermore, apoptotic bodies were observed in the testis of 72 h and 96 h of sleep-deprived animals. Conclusion: Outcome of the project reveals that out of 48 h, 72 h, and 96 h of SD, 96 h of SD has a great impact on sexual behavior, HPT hormones, and testicular morphology.